2020
DOI: 10.1002/gcc.22843
|View full text |Cite
|
Sign up to set email alerts
|

Immuno‐oncology gene expression profiling of formalin‐fixed and paraffin‐embedded clear cell renal cell carcinoma: Performance comparison of theNanoString nCountertechnology with targetedRNAsequencing

Abstract: Inflammatory gene signatures are currently being explored as predictive biomarkers for immune checkpoint blockade, and particularly for the treatment of renal cell cancers. From a diagnostic point of view, the nCounter analysis platform and targeted RNA sequencing are emerging alternatives to microarrays and comprehensive transcriptome sequencing in assessing formalin-fixed and paraffin-embedded (FFPE) cancer samples. So far, no systematic study has analyzed and compared the technical performance metrics of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Complementing and extending these studies, we compiled a retrospective cohort of carefully clinically annotated and confirmed ALK- and EGFR-positive NSCLC, molecularly analyzed at the Heidelberg routine diagnostic laboratory [ 22 ]. We profiled routine diagnostic formalin-fixed and paraffin-embedded biopsies after mutational analysis by NGS using the NanoString nCounter technology [ 36 ]. This technology, which can be directly applied in a routine diagnostic setting and is tissue sparing, facilitates focused analysis of mRNA profiles of 770 genes with fragmented nucleic acids as input material.…”
Section: Discussionmentioning
confidence: 99%
“…Complementing and extending these studies, we compiled a retrospective cohort of carefully clinically annotated and confirmed ALK- and EGFR-positive NSCLC, molecularly analyzed at the Heidelberg routine diagnostic laboratory [ 22 ]. We profiled routine diagnostic formalin-fixed and paraffin-embedded biopsies after mutational analysis by NGS using the NanoString nCounter technology [ 36 ]. This technology, which can be directly applied in a routine diagnostic setting and is tissue sparing, facilitates focused analysis of mRNA profiles of 770 genes with fragmented nucleic acids as input material.…”
Section: Discussionmentioning
confidence: 99%
“…A tissue surface area of approximately 50 mm 2 was used to harvest the necessary amount of RNA (~50 ng). RNA was input directly into the nCounter platform (NanoString Technologies, Seattle, WA) for the hybridization reaction [ 17 ]. Subsequent transcriptome analysis is based on the customized 289-immuno-gene panel (Supplemental Table 1 ), which includes 289 genes involved in the immune response in cancer for individual tumor samples.…”
Section: Methodsmentioning
confidence: 99%
“…NanoString nCounter is a recently developed technology combining single-molecule fluorescence imaging with highly specific and sensitive nucleic acid binding probes providing an accurate quantitative analysis of the expression of multiple genes from one sample [6]. Crucially, Nano-String molecular profiling works effectively on partially degraded and formalin-fixed, paraffin embedded (FFPE) post-mortem tissue and is robust to low-abundance RNAs, unlike other RNA sequencing technologies [7]. RNA was extracted from 2 Â 10 μm curls of FFPE tissue using the RNAStorm™ FFPE RNA extraction kit (Cell Data Sciences, Fremont, CA, USA) according to the manufacturer's guidelines.…”
Section: Transcriptional Analysismentioning
confidence: 99%
“…Post-mortem tissue can also be subject to substantial degradation bias, especially as ALS patients often die in an acidotic state (due to respiratory arrest) and thus are more prone to autolysis at post-mortem. Crucially, NanoString molecular profiling works effectively on partially degraded and formalin-fixed, paraffin embedded (FFPE) post-mortem tissue and is robust to low-abundance genes, unlike other RNA sequencing technologies [7].…”
Section: Reciprocal Changes In Regulators Of the Inflammasome Demonst...mentioning
confidence: 99%